1990
DOI: 10.1084/jem.172.6.1535
|View full text |Cite
|
Sign up to set email alerts
|

Vascular permeability factor: a tumor-derived polypeptide that induces endothelial cell and monocyte procoagulant activity, and promotes monocyte migration.

Abstract: SummarySystemic infusion of low concentrations of tumor necrosis factor/cachectin (TNF) into mice that bear TNF-sensitive tumors leads to activation of coagulation, fibrin formation, and occlusive thrombosis exclusively within the tumor vascular bed . To identify mechanisms underlying the localization of this vascular procoagulant response, a tumor-derived polypeptide has been purified to homogeneity from supernatants of murine methylcholanthrene A-induced fibrosarcomas that induces endothelial tissue factor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
373
1
20

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 775 publications
(405 citation statements)
references
References 36 publications
11
373
1
20
Order By: Relevance
“…Nevertheless, a recent report showed that activated monocytes and even dendritic cells, which are APC present at inflamed sites, expressed only Flt-1 and not Flk-1/KDR (47)(48)(49). VEGF may thus induce monocyte activation and migration via Flt-1 (47,50). This idea is supported by the finding that during the development of CIA, infiltration of the synovial tissue by monocytes and neutrophils occurs predominantly during the acute stage (51).…”
Section: Discussionsupporting
confidence: 63%
“…Nevertheless, a recent report showed that activated monocytes and even dendritic cells, which are APC present at inflamed sites, expressed only Flt-1 and not Flk-1/KDR (47)(48)(49). VEGF may thus induce monocyte activation and migration via Flt-1 (47,50). This idea is supported by the finding that during the development of CIA, infiltration of the synovial tissue by monocytes and neutrophils occurs predominantly during the acute stage (51).…”
Section: Discussionsupporting
confidence: 63%
“…Flt-1 is expressed by monocyte/macrophage, and VEGF can induce their migration across collagen membranes and endothelial cell monolayers (Clauss et al, 1990;Barleon et al, 1996). We showed that sFlt-1 gene transfer significantly attenuated infiltration of monocyte/macrophage both 1 and 7 days after stroke, which were associated with reduction in infarct size.…”
Section: Discussionmentioning
confidence: 99%
“…These were termed EMAP I-III and among these, EMAP I and II were novel cytokines, 1 whereas EMAP III turned out to be identical to the previously described VEGF. 29 EMAP II is a now well-characterized proinflammatory cytokine that inhibits tumor growth and metastasis by inhibition of angiogenesis. However, the precise signaling pathways for antiangiogenic activity of EMAP II have not yet been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%